2012
DOI: 10.11159/ijepr.2012.014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hydrolysis and Torrefaction on Pyrolysis Product Distribution of Spent Mushroom Compost (SMC)

Abstract: This study investigates the use of spent mushroom compost (SMC) as a potential feedstock for the production of bio-oil via fast pyrolysis process. It was found that, although SMC can be converted to bio-oil, due to its high moisture and ash contents, fast pyrolysis of SMC results in low yield and quality of bio-oil. Reduction of the moisture and ash contents in SMC is the key element to make SMC a desirable feedstock for biomass conversion. This investigation has revealed that pyrolysis of SMC that has been tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Table 1. The properties of mushroom spent compost (MSC) given in the literature [1,6,[9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Table 1. The properties of mushroom spent compost (MSC) given in the literature [1,6,[9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…One of the main studied objectives has been the bio-oil production through pyrolysis. Finney et al [88] and Garrido et al [89] compared different heat treatment technologies (pyrolysis and combustion) to determine an appropriate method of energy recovery from mushroom compost. In both cases under pyrolysis process a bio-oil with a low calorific value has been obtained.…”
Section: Thermogravimetry In Compost Bio-oil Productionmentioning
confidence: 99%
“…Torrefied biomass also contains improved grindability characteristics [38]. Recent studies have reported the effect of torrefaction pretreatment on biomass pyrolysis [27,[39][40][41][42]. While studies on biomass pretreatment by hydrolysis and by torrefaction have been reported, studies on combined hydrolysis and torrefaction are still limited.…”
Section: Introductionmentioning
confidence: 98%
“…All pyrolysis experiments were performed at 500 • C. The pyrolysis vapors were directly injected into the GC/MS (gas chromatography & mass Spectrometry) using helium as the carrier gas, in which the constituents of the pyrolysis vapor were separated in the GC column and identified. The method of chromatographic separation of pyrolysis products was adapted from Patwardhan [51] and previously used in other waste biomass studies done by the research group [27,42]. Py-GC/MS analytical procedure was explained thoroughly in Reckamp et al [42].…”
Section: Analytical Fast Pyrolysismentioning
confidence: 99%